Lifestyle and Psychological Factors Affecting Eating Habits and Physical Activity Among Government Servants in the States With the Highest Cumulative Cases in Malaysia During the COVID-19 Pandemic - Nur Hana Hamzaid; Nur Hana Hamzaid; Nur Hana Hamzaid; Zeesha Gloria Rayner Gumisi; Syaidatul Khafizah Ahmad Helme; Norhazirah Azmi; Mohd. Razif Shahril (Frontiers Media S.A., 2022)
IntroductionLike many other countries, the federal government of Malaysia took the initiative to implement nationwide home confinement as a preventive measure in response to the pandemic COVID-19 outbreak, better known as Movement Control Order (MCO). Many have suffered economically, which led to poor states of well-being. This study investigates the relationship between lifestyle, psychological factors affecting eating habits, and physical activity among government servants in states with the highest cumulative cases during the COVID-19 pandemic.MethodsA cross-sectional online survey was conducted among 210 government servants from four states (Selangor, Sabah, Kuala Lumpur, and Johor) from May 2021 to June 2021. Three validated questionnaires were used, namely, Emotional-Eater Questionnaire (EEQ), and Malay International Physical Activity Questionnaire (IPAQ-M) from López-Moreno et al. (1).ResultsThere were significant gender differences (P < 0.001) for supplement intake, with 30.4% among men and 62.3% in women. Almost half (49.1%) were classified as emotional or very emotional eaters. Also, a significant difference (P < 0.005) was found in the perception of boredom and apathy between men (35.7%) and women (31.8%). A majority (56.2%) stated that their mood positively affected their eating habits. The total metabolic equivalent of task (MET) for 132 subjects was 3495.8 ± 3862.7 min/week for physical activity. Significant differences were observed between MET and gender (Mann-Whitney U-test: P = 0.019), with men showing higher MET value (5001.4 ± 5354.0 min/week men, 2864.3 ± 2754.3 min/week women). A significant difference was observed among women for body weight and body mass index (BMI) before and during MCO (P < 0.001). For the emotional eater, there were correlations with eating habits before the MCO for quantity of food intake (P = 0.003), frequency of mealtime (P < 0.001), changes of food habits (P = 0.005), cooking methods (P = 0.016), and frequency of food intake (P = 0.020). There is no correlation (P = 0.577) between psychological factors affecting eating habits and physical activity during COVID-19.ConclusionChanges were reported before and during MCO on lifestyle, eating habits, and physical activity. Such information will help design strategies to improve the economic and health status among government servants in Malaysia during the implementation of MCO or something similar.